Classroom Languages As Used By English Teachers At An Indonesian Junior High School In Smpn 1 Keruak - Hadiatmi, Islamiyah; Wilian, Sudirman; Yusra, Kamaludin (Jurnal Ilmiah Pendidikan Indonesia, 2020)
The purposes of this study are to: (1) analyze the types of classroom languages as used by an English teacher during the teaching-learning process in the classroom; (2) describe the way the teachers use classroom languages; and (3) describe are those classroom languages used classifiable based on student levels. It employed a descriptive qualitative method. The object of this study was 3 English teachers at SMPN 1 Keruak. The data were collected by using an audio-video recording, field notes, and interview. The result of this study showed that (1) The English teacher employed 5 features of languages during the teaching process in the classroom those are Indonesia, English, Arabic, Sasak and Mixed languages. In each of the classes that observed showed that teachers almost used similar types of classroom languages. (2) The way the teacher employed classroom languages differently in each grade. (3) The classroom languages applied by the teacher during the teaching and learning process were employed based on students’ level.